1996
DOI: 10.1111/j.1469-8749.1996.tb15047.x
|View full text |Cite
|
Sign up to set email alerts
|

THE STABILITY AND EQUIVALENCE RELIABILITY OF THE FUNCTIONAL INDEPENDENCE MEASURE FOR CHILDREN (WeeFIM)®

Abstract: SUMMARY The reliability of the Functional Independence Measure for Children (WeeFIM) was examined in 37 non‐disabled children and 30 children with disabilities, from 12 to 76 months of age. The WeeFIM is derived from the Functional Independence Measure (FIM) and includes 18 items involving six functional subscalcs. Stability was assessed by administering the WeeFIM instrument to each child's caregiver on two occasions separated by 7 to 14 days. Intraclass correlation co‐efficients (ICCs) for individual items r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(40 citation statements)
references
References 17 publications
(4 reference statements)
1
37
0
Order By: Relevance
“…Moreover, clinicians are retested every 2 years with a different version of the examination to ensure their rating accuracy of the FIM. A number of studies have shown that the FIM has good interrater or test-retest reliability (>0.90) [21][22][23][24]. In contrast, for MDS assessments, each unit's assessment coordinator may obtain information from other staff orally or have specific professionals rate relevant items.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, clinicians are retested every 2 years with a different version of the examination to ensure their rating accuracy of the FIM. A number of studies have shown that the FIM has good interrater or test-retest reliability (>0.90) [21][22][23][24]. In contrast, for MDS assessments, each unit's assessment coordinator may obtain information from other staff orally or have specific professionals rate relevant items.…”
Section: Discussionmentioning
confidence: 99%
“…It is part of the Uniform Data System for Medical Rehabilitation. It has extensive evidence of reliability, validity, and responsiveness to change during inpatient rehabilitation for children and youth with TBI (Chen et al, 2005;Massagli et al, 1996;Ottenbacher et al, 1996Ottenbacher et al, , 1997Ottenbacher et al, , 2000Rice et al, 2005;Swaine et al, 2000;Ziviani et al, 2001), with established normative data (Msall et al, 1994). The WeeFIM is the pediatric downward extension of the FIMÔ (Granger, 1998), which was recommended as a core measure for adults with TBI (Wilde et al, 2010), but scoring criteria are somewhat different to account for developmental differences.…”
Section: Adaptive and Daily Living Skillsmentioning
confidence: 99%
“…The convergent and divergent validity of the LIFE-H was tested by comparing its scores with those of two instruments administered during the first testing session: the Pediatric Evaluation of Disability Inventory (PEDI) 20 and the Functional Independence Measure for Children (WeeFIM). 21 RECRUITMENT AND DATA COLLECTION PROCEDURES The research protocol was approved by the Research Ethics Committee of the three rehabilitation centers. For the reliability and construct validity procedures, recruitment was carried out with parents whose children had received therapy in clinical settings and who corresponded to one of the five diagnostic groups (CP, myelomeningocele [MMC], sensorymotor neuropathy, traumatic brain injury, and developmental delay).…”
Section: Content Validity Processmentioning
confidence: 99%